Platelets and their chemokines in atherosclerosis—clinical applications - von Hundelshausen, Philipp; Schmitt, Martin M. N. (Frontiers in Physiology, 2014)
The concept of platelets as important players in the process of atherogenesis has become increasingly accepted due to accumulating experimental and clinical evidence. Despite the progress in understanding the molecular details of atherosclerosis, particularly by using animal models, the inflammatory and thrombotic roles of activated platelet s especially in the human system remain difficult to dissect, as often only the complications of atherosclerosis i.e. stroke and myocardial infarction are definable but not the plaque burden. Platelet indices including platelet count and mean platelet volume and soluble mediators released by activated platelets are associated with atherosclerosis. The chemokine CXCL4 has multiple atherogenic activities e.g. altering the differentiation of T cells and macrophages by inhibiting neutrophil and monocyte apoptosis and by increasing the uptake of oxLDL and synergizing with CCL5. CCL5 is released and deposited on endothelium by activated platelets thereby triggering atherogenic monocyte recruitment, which can be attenuated by blocking the corresponding chemokine receptor CCR5. Atheroprotective and plaque stabilizing properties are attributed to CXCL12, which plays an important role in regenerative processes by attracting progenitor cells. Its release from luminal attached platelets accelerates endothelial healing after injury. Platelet surface molecules GPIIb/IIIa, GP1bα, P-selectin, JAM-A and the CD40/CD40L dyade are crucially involved in the interaction with endothelial cells, leukocytes and matrix molecules affecting atherogenesis. Beyond the effects on the arterial inflammatory infiltrate, platelets affect cholesterol metabolism by binding, modifying and endocytosing LDL particles via their scavenger receptors and contribute to the formation of lipid laden macrophages. Current medical therapies for the prevention of atherosclerotic therapies enable the elucidation of mechanisms linking platelets to inflammation and atherosclerosis